KH. Nasihun Amin’s Leadership in Shaping Student Character (Journal Of Islamic Education And Pesantren, 2025)
Kyai is the central leader who plays a dominant and strategic role in the management and sustainability of Islamic boarding schools. As the highest authority, the kyai becomes the main reference in organizing educational, religious, and social activities within the pesantren environment. The continuity and development of an Islamic boarding school are highly dependent on the leadership of the kyai, particularly in shaping the character of the santri. Pesantren are inherently recognized as character-forming institutions, where values such as discipline, responsibility, and moral conduct are cultivated through daily life and structured guidance. Therefore, strong direction and guidance from the kyai are essential in the character development process. This study employed a descriptive qualitative research design. Data were collected through observation, interviews, and documentation involving the kyai, ustadz, ustadzah, community members, and santri at Pondok Pesantren Sunan Bonang Mojojejer, Mojowarno, Jombang. The findings indicate that the kyai’s leadership in shaping santri character is characterized by strong charisma combined with a democratic leadership style modeled after the leadership of Prophet Muhammad SAW. As a result, santri at Pondok Pesantren Sunan Bonang demonstrate key character traits, including discipline, independence, tolerance, and responsibility. Supporting factors include the kyai’s efforts to improve facilities and learning resources, while limitations remain related to infrastructure development.